2013
DOI: 10.15376/biores.8.2.2351-2365
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of High Density Polyethylene (HDPE) Reinforced with Banana Peel Fibers

Abstract: Lignocellulosic fibers from banana peels were washed with water in order to increase their compatibility with a polymeric matrix, and their properties were compared with unwashed fibers. Washed banana fibers were mixed with high density polyethylene (HDPE) and placed in an injector chamber to produce specimens for tensile tests. Samples of washed banana fibers/HDPE composites were characterized by tensile tests and thermal analysis. The chemical composition of unwashed and washed banana fibers was analyzed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 23 publications
(31 reference statements)
3
19
1
Order By: Relevance
“…Vegetal fibers can be used in a wide range of application such as filters for heavy metals retention [86] , crafts, and as reinforcement to produce polymer matrix composites [95] .…”
Section: Lignocellulosic Fibers As Reinforcement In Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetal fibers can be used in a wide range of application such as filters for heavy metals retention [86] , crafts, and as reinforcement to produce polymer matrix composites [95] .…”
Section: Lignocellulosic Fibers As Reinforcement In Compositesmentioning
confidence: 99%
“…Besides mentioned fibers, every day new fibers appear as an alternative to produce natural composites, in literature there are studies with palmers fibers [41] , wheat straw [117] and rice straw [190] , pineapple crown [41] , banana pseudostem [186,191] , banana pells [95] and many other fibers can be extracted from different regions of the world.…”
Section: Lignocellulosic Fibers As Reinforcement In Compositesmentioning
confidence: 99%
“…The authors suggested incorporating BP in aqua feed formulation. HDPE and epoxy composite reinforced with BP fibers had improved mechanical properties (Naidu et al 2013, Pereira et al 2013.…”
Section: Other Usesmentioning
confidence: 99%
“…Natural fiber reinforced polymer matrix got considerable attention in numerous applications due to its good properties and superior benefits of natural fiber over synthetic fibers. Besides the advantages of eco-friendly and biodegradability, fiber reinforced polymer are low weight, low cost, high specific strength, non-abrasive, fairly good mechanical properties such as tensile modulus and flexural modulus, improved surface finish of molded parts composite, renewable resources, flexibility during processing, being abundant, and also minimal health hazards [9].…”
Section: Introductionmentioning
confidence: 99%